OBSERVASI DAN UJI COBA TEKNIK ANYAMAN BAMBU PADA PENGRAJIN DI KECAMATAN PANONGAN, KABUPATEN TANGERANG - Junianto, Aloysius Baskoro; Ho, Yunita (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Bamboo woven crafts are one of the typical craft in the Panongan District area, Tangerang Regency, Banten since long time ago. The culture was handed down from generation to generation and becoming local wisdom until now. Today, these bamboo woven products are difficult to compete, due to the absence of innovation and product development. Therefore bamboo craftsmen in Panongan need a new strategy to improve competitiveness through design innovation and development of their woven products. This strategy is needed so the business can sustain and grow. In addition, some efforts are needed in order to identify the situations and conditions and to discover the potential for further development of the woven products. This study is aimed to attempt observations as well as trials on the capabilities of the bamboo woven techniques within craftsmen in the villages of Ciakar and Ranca Kelapa in Panongan District. From the observation results; it is showing that the woven technique of craftsmen in the villages of Ciakar and Ranca Kelapa have potentials to be developed into more valuable products. In general, the craftsmen have good skill and able to develop new technique. This skill could be taken into account as strategy to develop new product by product designer in the future.